Avaliação dos efeitos associados dos inseticidas fipronil e imidacloprido sobre a mortalidade da abelha nativa Melipona scutellaris (Latreille, 1811) - Costa, Leticia Mariano da (2015)
Bees are social insects of fundamental importance to the environment, because they are responsible for pollinating more than 70% of existing agricultural crops in the world. Brazil is the country with the highest number of described species, with representatives of most families. Among representatives of the Apidae family, is the Melipona scutellaris specie, commonly known as "uruçu" or "uruçu do Nordeste”, it is easy to handling and very well adapted to the climate of the state of São Paulo. However, due to the intensive use of pesticides, native bees are suffering the consequences, because, although they are not the target of insecticides, are highly vulnerable to contamination. Among the insecticides developed in the 90s, the neonicotinoids and fipronil have been identified as the main substances involved in collapse, and were suspended in 2013 in the European Union for two years for best evaluation. These insecticides are often used simultaneously, so bees can be contaminated with both molecules. Due to this fact, the aim of this study was determine the median lethal time (LT50) of fipronil and imidacloprid insecticides separately and synergistically on forage bees of M. scutellaris. For this, was obtained only the LD50 and LC50 of imidacloprid, according to the rules of the OECD, because values of fipronil were established by Lourenço et al. (2012a, 2012b). The LD50 of imidacloprid obtained was 2.41 ng a.i. / bee (24 hours) and 1.29 ng a.i./ bee (48 hours). The LC50 value found was 2.01 ng a.i./μL diet (24 hours) and 0.81 ng a.i./μL diet (48 hours). These data indicate that M. scutellaris specie is more sensitive to the insecticide imidacloprid that A. mellifera africanized. From these values, was obtained the LT50 based on topical and oral contamination of fipronil and imidacloprid insecticides and also these substances acting together. The results showed that fipronil has LT50 greater than imidacloprid. When acted in combination to LT50 presented intermediate values between the LT50 fipronil and imidacloprid, isolated. Then, according to the values obtained, there was not synergy, but a decrease in the toxicity of imidacloprid.